Sosialisasi Sistem Penanaman Hidroponik Limbah Tebu di Gampong Sidorejo, Langsa, Aceh - Vivi Mardina; . Fitriani; . Muslimah (Institut Pertanian Bogor, 2019)
Hydroponic is the method to cultivate plant by using media supplied with nutrient solution and or media other than soil. One of the options for soil replacement is sugarcane waste. Sugarcane waste or bagasse is residue from the sugar mill (Saccharum oficiarum) processing. The objective of this community service program (PKM) is to transfer knowledge and skills to the Sidorejo community to cultivate using a hydroponic system by utilizing bagasse as planting medium in order to manage sustainable environment. The main target of this PKM program is the group of PKK Gampong Sidorejo. The method used includes lectures, direct practice, and discussion. The results of the activity concluded that 1) Participants' knowledge of hydroponic cultivation using bagasse increased by about 20; 2) This activity has benefit the Sidorejo community, particularly PKK group with an increase in the willingness of participants to attend similar training around 98 and; 3) Planting a hydroponic system can be used as a means of channeling hobbies, health, and can be developed into a business scale.